Metastatic germ cell tumor with complete response-7 years follow up - Jakovljevic, Branislava Golub; Đokanović, Dejan; Miličević, Snježana; Škobić, Anđa; Ćazić, Dejan; Krivokuća, Vladimir (International Journal of Research in Medical Sciences, 2017)
Cancer of the testis is a relatively uncommon disease, accounting for approximately 1-1.5% of all cancers in males. 5% of the malignant germ cell tumors are made of extragonadal origin. Germ cell tumors occur in men younger, usually between 20 and 35 years old. We report a case of a patient with metastatic extragonadal germ cell tumor with multiple sites of metastases, and very high initial values of tumor marker human chorionic gonadotrophin (HCG)- 1351308. At the time of diagnosis, the patient was in a very poor general condition. After the applied chemotherapy, there was a complete response and 7 years later the patient is without any symptoms of disease.